2018
DOI: 10.3389/fmicb.2018.02025
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Rhodotorula mucilaginosa to Patulin Based on Lysine Crotonylation

Abstract: Patulin (PAT) is a mycotoxin produced by some Penicillium, Aspergillus, and Byssochlamys species. Rhodotorula mucilaginosa is able to degrade PAT in vivo as well as in vitro, up till date, the process and molecular mechanism(s) involved patulin degradation still remains unknown. Protein lysine crotonylation (Kcr) plays an important role in regulating chromatin dynamics, gene expression, and metabolic pathways in mammals and eukaryotes. Investigation of the Kcr changes accompanying degradation of patulin in R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…In recent years, several landmark studies have revealed dramatically improved number of crotonylated lysine residues and crotonylated proteins (Table 1), and these proteins play roles in nearly all cellular processes including chromatin remodelling, metabolism, cell cycle and cellular organization. [13][14][15][16][17][18][19][20][21][22] Crotonylome mapping provides an important resource for discovering novel properties and regulatory functions of crotonylation.…”
Section: Protein Crotonylomementioning
confidence: 99%
“…In recent years, several landmark studies have revealed dramatically improved number of crotonylated lysine residues and crotonylated proteins (Table 1), and these proteins play roles in nearly all cellular processes including chromatin remodelling, metabolism, cell cycle and cellular organization. [13][14][15][16][17][18][19][20][21][22] Crotonylome mapping provides an important resource for discovering novel properties and regulatory functions of crotonylation.…”
Section: Protein Crotonylomementioning
confidence: 99%
“…Several recent reports have shown that crotonylation plays an important role in the regulation of various biological processes in humans, animals [19], plants [18,22] and microorganisms [21].…”
Section: Discussionmentioning
confidence: 99%
“…Global profiling of crotonylation has been reported in tobacco [18], zebrafish [19], rice [20], yeast [21], and papaya [22], which showed that crotonylation plays an important role in the regulation of various biological processes across kingdoms.…”
mentioning
confidence: 99%
“…Research on molecular mechanisms can ensure the sustainable development of biotechnology by serving as an inexhaustible source of information. Some current trends in the elucidation of mechanisms are presented: the mechanism of PAT degradation by yeast (Chen et al., 2017; Ianiri et al., 2013; Wang et al., 2019; Yang et al., 2018), mechanism of PAT biosynthesis (Li et al., 2019; Tannous et al., 2018), mechanism of PAT toxicity (Figure 1) (Ramalingam et al., 2019), the biocontrol mechanism (Zhang et al., 2018), mechanism of PAT adsorption by bacteria (Wang, Yue et al., 2015). There are confirmed biotechnological methods that are less used in PAT control.…”
Section: Future Aspects For Biotechnology Development To Overcome Thementioning
confidence: 99%
“…Peptide networks can be useful in PAT control because post‐translational modifications (PTMs) are important in the cellular mechanism (Mauser & Jeltsch, 2019). For example, peptide arrays could be helpful in the study of PTMs during PAT degradation by R. mucilaginosa (Yang et al., 2018).…”
Section: Future Aspects For Biotechnology Development To Overcome Thementioning
confidence: 99%